Document authentication at molecular levels using desorption atmospheric pressure chemical ionization mass spectrometry imaging. (30th August 2013) - Li, Ming; Jia, Bin; Ding, Liying; Hong, Feng; Ouyang, Yongzhong; Chen, Rui; Zhou, Shumin; Chen, Huanwen; Fang, Xiang
Abstract : Molecular images of documents were obtained by sequentially scanning the surface of the document using desorption atmospheric pressure chemical ionization mass spectrometry (DAPCI‐MS), which was operated in either a gasless, solvent‐free or methanol vapor‐assisted mode. The decay process of the ink used for handwriting was monitored by following the signal intensities recorded by DAPCI‐MS. Handwritings made using four types of inks on four kinds of paper surfaces were tested. By studying the dynamic decay of the inks, DAPCI‐MS imaging differentiated a 10‐min old from two 4 h old samples. Non‐destructive forensic analysis of forged signatures either handwritten or computer‐assisted was achieved according to the difference of the contour in DAPCI images, which was attributed to the strength personalized by different writers. Distinction of the order of writing/stamping on documents and detection of illegal printings were accomplished with a spatial resolution of about 140 µm. A Matlab® written program was developed to facilitate the visualization of the similarity between signature images obtained by DAPCI‐MS. The experimental results show that DAPCI‐MS imaging provides rich information at the molecular level and thus can be used for the reliable document analysis in forensic applications. © 2013 The Authors. Journal of Mass Spectrometry published by John Wiley & Sons, Ltd.